IMPACT OF E-LEARNING PLATFORMS ON STUDENTS’ ACADEMIC PERFORMANCE IN NNAMDI AZIKIWE UNIVERSITY, AWKA, ANAMBRA STATE, NIGERIA (Journal of the Management Sciences, 2024)
This study investigated the impact of e-learning platforms on academic Performance of undergraduates in Nnamdi Azikiwe University, Awka. The specific objectives examined the various e-learning platforms utilized in tertiary institutions and the strategies for improving the utilization of e-learning platforms in tertiary institutions. Lack of internet facilities, technology and e-learning facilities have been identified as major problems of adopting or fully utilizing online e-learning platforms by most Nigerian Universities. Elearning platforms such as Zoom, Microsoft teams, Udemy, Coursera have been recognized to improve students’ academic performance to a great extent. The population made up of 2,358 (Two thousand, three hundred and fifty-eight) regular undergraduate students from selected faculties in Nnamdi Azikiwe University. Questionnaire was used to collect data. Descriptive statistics was employed using simple descriptive statistical tools, such as frequency distribution scale, likert scale and simple percentage. The results revealed that: a good number of e-learning platforms (Zoom, Microsoft Teams, Udemy, Cousera) have been utilized by undergraduates as shown by mean value of 3.21; and there were recognized strategies (provision of more e-learning facilities and internet services) that should adopted to improve the continuous utilization of e-learning platforms among undergraduates (with a mean value of 3.18) in Nnamdi Azikiwe University, Awka with a mean value of 3.17. This study recommended inter alia that government should assist in supporting tertiary institutions with financial services and management experts to promote and sustain the use of e-learning platforms in tertiary institutions.
Keywords: E-learning, students’ academic performance, Unizik, Awka, Nigeria.